Pengaruh Implementasi Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Kinerja Pegawai Pada Direktorat Jenderal Pengawasan Sumber Daya Kelautan Dan Perikanan - Hamimi Marha; Muhammad Arif; Kusmilawaty Kusmilawaty (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research tries to understand how the performance of workers at the Directorate General of Marine and Fisheries Resources Supervision has changed after the implementation of internal controls and accounting information systems. The main method of collecting data in this quantitative research is through distributing questionnaires. In this study, which had 46 participants, a simple random selection procedure was used to select the sample. The techniques used to evaluate hypotheses include statistical tests (T, F, and R tests), multiple analysis tests, and conventional assumption tests of multicollinearity, heteroscedasticity, and normality. Utilizing SPSS Version 25, assisted data analysis. Based on the data classification findings, it appears that the choice of saving is simultaneously influenced by characteristics such as religion, education and ethical awareness. The accounting information system component (X1) which has a sig value of 0.003 is partially responsible for the positive and substantial influence on saving preferences. With a sign value of 0.000, the education component (X2) has a relevant impact and has a positive impact on savings preferences. The dependent component is close to 1 and the coefficient of determination (R2) is 0.660, this proves that the independent component and dependent component have a relevant correlation. The Accounting Information System component (X1) has a strong and beneficial impact on employee performance (Y) at the Directorate General of Marine and Fisheries Resources Supervision. The internal control component (X2) has a positive and relevant impact on employee performance (Y) at the Directorate General of Marine Resources and Fisheries Supervision.